Decision-Making and Incentives in ESG-Oriented Firms: Impacts on Executive Pay-for-Performance Sensitivity - Rongyan Zhang; Liu Yang; Jiafu Su (Decision Making: Applications in Management and Engineering, 2024)
The adoption of ESG principles plays a crucial role in advancing the high-quality development of enterprises. This research examines the influence of ESG implementation on the sensitivity of executive compensation to performance, alongside the underlying mechanisms of their interaction. The findings demonstrate that improved ESG performance is significantly linked to a heightened alignment between executive remuneration and organisational performance. ESG initiatives appear to positively influence the structuring of compensation agreements. Further analysis shows that ESG practices enhance this pay-for-performance sensitivity by increasing corporate transparency and mitigating excessive executive pay. The heterogeneity analysis indicates that the positive impact of ESG on executive compensation sensitivity is more pronounced in non-state-owned enterprises, firms operating within less transparent information environments, and those characterised by labour-intensive operations. This research deepens the understanding of the microeconomic implications of ESG adoption and offers theoretical support for both regulatory ESG frameworks and corporate engagement in sustainable practices.